Teen idol - Cabot, Meg (HarperCollins, 2004)
High school junior and columnist for the school newspaper, Jenny Greenley is good at dispensing advice to others, but when nineteen-year-old film heartthrob Luke Striker pays a visit to research a role, he creates such havoc that not even Jenny is sure she can fix it.